Human microbiota-associated animal models: a review - Huang, Xiangning; Yu, Yunfeng; Tian, Na; Huang, Jiawang; Zhang, Xiaoqin; Yu, Rong (Frontiers in Cellular and Infection Microbiology, 2025)
Human microbiota-associated (HMA) animal models have become indispensable tools for investigating microbe-host interactions and disease pathogenesis. However, standardization challenges persist across different research groups when such models are used in fecal microbiota transplantation (FMT) protocols. Establishing a successful HMA model involves multiple stages, including donor screening, fecal suspension preparation, recipient preparation, and FMT. The outcomes of these stages are influenced by donor characteristics, recipient type, microbial viability, and dietary factors. This review examined the critical components of HMA model production, including the inclusion and exclusion criteria for human donors, collection time and processing methodology for fecal samples, recipient animal preparation strategies, and FMT regimens with engraftment validation. The key findings revealed that short-term antibiotic, probiotic, or laxative use constitutes an essential donor exclusion criterion. The time and method of fecal collection should be standardized as much as possible. Fecal samples should be processed as soon as possible, in anaerobic environments, with the addition of suitable protectants if they must be preserved at low temperatures. Microbial community profiling via 16S rRNA gene sequencing represents the primary method for analyzing microbiome composition and verifying microbiota engraftment efficacy throughout FMT procedures. The most commonly used recipients for HMA modeling included germ-free and pseudo-germ-free animals generated through antibiotic-mediated microbiota depletion. Although FMT with a single gavage of fecal suspension proved sufficient for model establishment, multiple frequencies and longer FMT durations significantly improved the efficiency of donor microbiota colonization. Overall, these findings are expected to aid the establishment of a standardized and reproducible protocol for preparing HMA models.